Analysis Of Service System Development For Pregnant Women Handled By PSC In Mimika Regency Year 2024 - Rena, Rena; P.A. Kodrat Pramudho (Jurnal EduHealth, 2024)
Introduction: Mimika Regency, Central Papua Province, is one of the districts with a fairly high maternal mortality rate. The aim of this research is to analyze the public's understanding of the signs of an emergency in providing assistance to pregnant women in Mimika, to assess pregnant women's understanding of the service system at the PSC in Mimika and to analyze the development of the service system at the Public Safety Center (PSC) 119 Mimika in providing assistance to pregnant women in Mimika. Method: This research uses a qualitative method approach involving PSC 119 Mimika officers and pregnant women handled by PSC 119 Mimika with 5 informants in each section. Data collection was carried out by means of observation, in-depth interviews and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions or verification. Results: Research shows that public understanding of the signs of an emergency in providing assistance to pregnant women in Mimika is influenced by education and knowledge, access to information, access to health services, communication and education, experience, and cooperation between the parties. Pregnant women's understanding of the service system at PSC 119 Mimika is influenced by service availability, accessibility, service quality, availability of information, and participation of pregnant women with related parties. Development of the service system at PSC 119 Mimika in providing assistance to pregnant women in Mimika in the form of increasing accessibility, increasing service availability, improving service quality, developing educational programs, developing health information systems, and reporting and monitoring systems.